Evaluation of natural dyes extracted from beets for their potential use in an isotonic drink (Agroindustria, Sociedad y Ambiente, 2023)
With the objective of evaluating the dyes extracted from beetroots to incorporate them into an isotonic drink, a research work was conducted in four (4) phases. These dyes, being of natural origin, are ideal substitutes for artificial dyes and you can take advantage of their potential health benefits, such as their antioxidant and anti-cancer properties. The first phase consisted of the physicochemical characterization of the raw material, with results of 6.5 ± 0.1 pH, 5.0 ± 0.7 °Brix, 0.048 ± 0.004 % of titratable acidity and 89.8 ± 0.4 % humidity. The second was divided into two stages, selection of the mixture of solvents and the proportion vegetable: solvents mixture, the mixture of proportions by volume selected was 62: 37.7: 0.3 of water, ethanol and acetic acid and the optimal vegetable: solvent mixture ratio was the 1:1 ratio, they were extracted with concentrations (mg/L) of 176 ± 4 and 173 ± 2 of betacyanins and betaxanthins, respectively. Anthocyanins were not detected. In phase three (3), four (4) isotonic drinks were formulated, obtaining that the formula with the highest acceptability was that of 0.1% dye extract. For the final phase, the drinks were stored for two (2) weeks at room temperature (23°C) and their color was measured in the LAB space, the "L" parameter increased from the second day of storage, while the parameter "a" decreased, in the case of "b", it had constant values for two of the drinks evaluated. It was concluded that the natural dyes extracted from beetroots can be used in the preparation of an isotonic drink.
Keywords: betacyanins, betalains, betaxanthins, isotonic drink, natural dyes